Assessing Earnings Quality Using Accruals and Sustainability Metrics - Louissia Mia Aulia Farasthy Kusnadi; Kusuma Indawati Halim (JAS (Jurnal Akuntansi Syariah), 2026)
Purpose – This study intends to investigate the extent to which managerial ownership, free cash flow and leverage influence earning quality that is measured using the operating accruals and earnings sustainability, with profitability as moderating variable and firm size as a control variable. This study centers on the Indonesian transportation and logistics industry, since governance complexity makes revealing reporting an essential requirement. Method – The analysis uses panel data consisting of 34 companies listed on the Indonesia Stock Exchange in 2020 to 2024. Data The data contains 170 observations from several years for different firms. Multiple regression and moderated regression models are used in this study. Operating accruals measures and earnings sustainability are used to measure the quality of earnings, by using profitability to test for moderating effect. Findings – Test results confirm that free cash flow and leverage are negatively associated with operating accruals and there is no significant effect of managerial ownership. Leverage has a significant positive impact on earnings sustainability, and managerial ownership and free cash flow do not have any significant effects. Profitability strengthens the free cash flow pathway to earnings sustainability and weakens leverage. Firm size is not a major driver for either of these earnings quality measures. Implications – The results imply that the value of reported earnings is conditional on financial decisions and ownership structure and therefore affect earnings quality. Managers can assess the impact of leverage and free cash flow on financial reporting. These findings are useful to investors when measuring a firm’s financial quality in the process of making investment decisions. For regulators, the results emphasize the importance of enhancing disclosure rules and overseeing practices to ensure transparent and long-lasting reporting practices. This paper adds to knowledge of the importance of governance and financial determinants in the determination of earnings quality in emerging countries.